KP Pengaruh Promosi, Kemudahan Penggunaan dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Tokopedia di Kabupaten Kudus - Suroso, Iwan; Tsamama Ghina Ramandha (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of promotion, ease of use, and consumer trust on purchasing decisions among Tokopedia users in Kudus Regency. The background of this research is based on the rapid development of e-commerce in Indonesia, where purchasing decisions are increasingly shaped by digital marketing strategies, technological usability, and consumer perceptions of trust and security. A purposive sampling technique was applied to obtain 120 respondents who had made at least one purchase through Tokopedia within the last six months. Data were collected through structured questionnaires and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and the coefficient of determination test with the assistance of SPSS version 29. The findings revealed that, partially, ease of use and consumer trust significantly and positively influenced purchasing decisions, emphasizing the importance of user-friendly platforms and consumer confidence in online transactions. In contrast, promotion did not show a significant direct effect, indicating that consumers may prioritize trustworthiness and usability over promotional offers when making purchase decisions. However, when tested simultaneously, promotion, ease of use, and consumer trust collectively demonstrated a significant and positive impact on purchasing decisions. These results highlight that while individual promotional strategies may not be decisive, their combined effect alongside usability and trust contributes to shaping consumer behavior. This study concludes that Tokopedia and similar e-commerce platforms should focus on enhancing user experience and building consumer trust, while integrating promotions strategically as complementary support to strengthen purchasing decisions in the digital marketplace.